Battle of Islamic Women's Discourse through Popular Culture in Post-authoritarian Indonesia - Dian Rizky Azhari; M. Yoesoef (Universitas Sebelas Maret, 2022)
After the collapse of the New Order, the debate on the discourse of Islamic women developed rapidly in various directions due to the influence of ideas from both the East and the West. Islamic thinkers from within the country are being challenged by the massive influence of global Islamism and the entry of modern western culture. This very complicated battle caused each faction of thought to have to find a way to speak up and propagate their discourse in the public sphere. The most appropriate tool to spread ideology in the midst of the development of society and technology is through popular culture. It can be seen that since the collapse of the New Order, each faction of thought propagated their version of discourse through literary works, magazines, films, entertainment programs on television, social media, to everyday commercial products through their advertisements and taglines. Most of the issues they dispute relate to the role of Islamic women, women's relationships with Muslim men, daily practices as Islamic women, and the image of Islamic women, such as the use of the hijab, clothing and accessories. The results of the research then show that although there are many outside thoughts that enter Indonesian society, the discourse of Islamic women in the traditional-moderate version of Islam as a thought that has long existed in Indonesia is still the majority discourse in society.